Isu Saudara Baru dalam Media Islam - Siren, Nor Raudah (Jurnal Usuluddin, 2000)
This article deals with issues concerning Muslim converts based on four Islamic magazines, i.e al-Islam, Dakwah, Ummi and Cahaya. The purpose of this article is to provide Muslim readers, researchers and da'i an information about Muslim converts, their problems and needs.